2012
DOI: 10.1002/cssc.201100453
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Tagged Iron Complex‐Catalyzed Epoxidation of Olefins in Imidazolium‐Based Ionic Liquids

Abstract: A new ionophilic ligand and a new ionically tagged imidazolium-based iron(III) complex were synthesized and applied in the air oxidation (also hydrogen peroxide) of alkenes in imidazolium-based ionic liquids. At least ten recycling reactions were performed. The epoxidized olefin was obtained in very good yields of 84-91 %. Some important mechanistic insights are also provided based on electrospray ionization quadrupole-time of flight mass spectrometry for the oxidation reaction. These results indicate that oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…For instance, we have shown that BMI.InCl 4 is capable of promoting the tetrahydropyranylation of alcohols [12], in situ generation and stabilization of iminium ions [13] and to copromote the formation and stabilization of charged-intermediates during transesterification reactions [14]. We have also recently investigated iron-based ILs as catalysts for oxidation [15], reduction [16] and multicomponent reactions [17][18][19]. In this sense, we have therefore envisaged that the iron-containing ILs could also work as efficient catalysts for the styrene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have shown that BMI.InCl 4 is capable of promoting the tetrahydropyranylation of alcohols [12], in situ generation and stabilization of iminium ions [13] and to copromote the formation and stabilization of charged-intermediates during transesterification reactions [14]. We have also recently investigated iron-based ILs as catalysts for oxidation [15], reduction [16] and multicomponent reactions [17][18][19]. In this sense, we have therefore envisaged that the iron-containing ILs could also work as efficient catalysts for the styrene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…2 On the other hand, the main challenge of modern catalysis is to achieve environment-friendly processes, using sustainable resources and very active catalysts. [3][4][5][6] In this regard, biopolymers are attractive for use combined with transition metal catalysts for further applications in organic synthesis, fine chemical and flow reactors, [7][8][9][10][11][12][13][14] and cellulose may have a great potential of use in heterogeneous catalysis. The formation of bonds catalyzed by transition metals is considered one of the most important processes in synthetic chemistry, helping to build complex molecules structures from simple precursors.…”
Section: Introductionmentioning
confidence: 99%
“…We have also explored the chemistry of TSILs applying some derivatives as catalysts for multicomponent reactions, [60][61][62] as ligands for organometallic investigations, 63 as reagents for organic reactions mechanistic evaluations, [64][65][66] as ligands for the formation of water-soluble lanthanide-based fluorescent probes, 67 and others. [68][69][70] Motivated by their importance, and due to limited knowledge of the organizational, supramolecular interactions and physicochemical properties of TSILs, we have recently studied the structural organization and supramolecular interactions of the TSIL 1-methyl-3-carboxymethylimidazolium chloride. 71 Herein we wish to expand the knowledge of TSIL chemistry by disclosing a novel study on the supramolecular interactions and aggregate formation/stabilization of an imidazolium-based TSIL (Figure 1) derived from the natural kojic acid.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70] Due to our interest in the chemistry of MIK.Cl, we decided to perform a comprehensive evaluation of its properties in solid, solution and gas phase interactions by using a set of techniques formed by single-crystal X-ray diffraction, nuclear magnetic resonance (NMR) spectroscopy, UV-Vis spectrophotometry, conductivity measurements, small angle X-ray scattering (SAXS), electrospray (tandem) mass spectrometry (ESI-MS(/MS)), and theoretical calculations. The structural organization and supramolecular interactions found for MIK.Cl nicely highlight the importance of H-bonds for the unique directionality of this important ionic compound, and details will be disclosed herein.…”
Section: Introductionmentioning
confidence: 99%